Comparison Of Metoclopramide and Dexamethasone in Post-Operative Vomiting: Comparison of Metoclopramide and Dexamethasone in Post-Operative Vomiting - Rab, Abdul; Parveen, Sughra; Iqbal, Mazhar; Ahmad, Tanveer; Ali, Asif; Waheed, Abdul (Pakistan BioMedical Journal, 2022)
Postoperative nausea and vomiting are one of the most common complaints following anesthesia and surgery. This study was designed to evaluate the efficacy of dexamethasone and metoclopramide to prevent postoperative vomiting (POV) in patients undergoing abdominal surgeries. Objective: To compare the efficacy of injection metoclopramide with injection dexamethasone for POV after abdominal surgeries. Methods: This Randomized Double-Blind Controlled Trial was conducted in ward 3, Jinnah Postgraduate Medical Centre, Karachi for one year., upon a sample of 98 patients, aged 12 to 60 years and undergoing abdominal surgery (elective and emergency) divided into two groups (Group A: Injection Metoclopramide 10 mg, and Group B: Injection Dexamethasone 8mg), of 49 patients each. The incidence of POV were recorded during the first 24 h postoperatively. Results: The mean age of the sample stood at 31 (SD ± 03) years, with most of the sample comprising of males (72.45%). Vomiting was noted in both groups, with group a reporting vomiting among 07 individuals and group B reporting vomiting among 09 individuals. There was no statistical difference between the incidences of vomiting in both groups. Conclusion: After careful consideration, it may be concluded that both agents, namely metoclopramide and dexamethasone are efficacious at minimizing the incidence of POV and hence both may be used interchangeably or in conjunction among patients undergoing abdominal surgeries